Training and Assistance in the Implementation of Interactive Learning Media and Utilization of Technology by Using the Wordwall Application - Fitrani, Laqma Dica; Al Hafidz, Mohammad; Muazaroh, Muazaroh; Iramani, Iramani; Karyawan, M Anang (STMIK Royal, 2023)
One of the impacts of the Covid-19 Pandemic is the change of learning process in elementary schools from offline learning to online learning. The results of the observations at Al-Khoiriyyah islamic elementary school show that partners still had difficulties in utilizing information technology facilities besides there was also a decrease in the enthusiasm of teachers and students in the learning process. The community service team offers solutions by providing training related to interactive learning media and the utilization of technology using the wordwall application. The wordwall application can attract the enthusiasm of teachers and students in the learning process by utilizing various features. This training was attended by 8 participants located at UHW Perbanas on June 24, 2022. The methods used were discussion, independent practice, and evaluation obtained from filling out the pre-test and post-test. The results of the training and mentoring show that 100% of the training participants are able to use wordwalls. The learning media using this wordwall had a significant effect and this was shown by the practical results of each participant who successfully completed the tasks given by the community service team which is 8 participants successfully made a quiz using the wordwall application.